Science Diplomacy in Ecuador: Political Discourse and Practices Between 2007 and 2017 - Bonilla, Kleinsy; Serafim, Milena; Bámaca-López, Efraín (Frontiers in Research Metrics and Analytics, 2021)
The decade 2007-2017 was a period in which the Republic of Ecuador experienced a series of economic, social, cultural, and political transformations. This research focused on science, technology, and innovation (STI) changes with implications for Ecuador’s foreign policy. One of the core components incorporated was Ecuador’s engagement with foreign governments and various regional and global actors to further scientific and technological advances. These far-reaching collaborations aimed to reduce gaps the country experienced in science and research. Moreover, to incorporate Ecuador into worldwide initiatives to tackle cross-border issues, such as climate change and environmental sustainability. These measures included academic and scientific mobility through an extensive scholarship program, the Prometeo Fellowship Program, the Yasuni ITT Initiative, the creation of emblematic research universities, and certain guidelines released by the Ministry of Foreign Affairs and Human Mobility of Ecuador related to these policies. This article reports on qualitative research in which President Rafael Vicente Correa Delgado’s political discourse was analyzed, along with key STI policies promoted in his administrations. The objective of this study was to establish different implications from the Science Diplomacy perspective (SD); particularly, reflecting on the consistency between the political rhetoric and the policy implementation. Evidence suggests that the political discourse materialized into concrete STI policies that could partially explain positive transformations in various aspects of the STI context in Ecuador. Institutional strengthening, international mobility (inward and outward), increased scientific output, and foreign policy practices involving SD which can be traced in the studied period. SD strategies could have been more effective and lasting if they were not discontinued upon Correa's departure from the Presidency.